Effect of carbonic anhydrase inhibitors on Anopheles albimanus larvae (Diptera: Culicidae) - Rocha O., Leonardo; Torres G., Carolina; Corena-McLeod, María; Vélez B., Iván D.; Robledo R., Sara M. (Revista Colombiana de Entomología, 2013)
Carbonic anhydrase (CA) catalyzes the reversible conversion of CO2 to bicarbonate and participates in mechanisms of alkalinization in the intestine of mosquitoes. The toxicity of four CA inhibitors (CAI ): acetazolamide (AZ M), methazolamide (MZM), ethoxolamide (ETX) and dorzolamide (DZA ) were evaluated in larvae of Anopheles albimanus by monitoring mortality 24, 48 and 72 hours post application, at a concentration of 50 ug/ml diluted in dimethyl sulfoxide previously. All IA C reduced the population of larvae in variable proportions. ETX showed the highest toxicity, achieving more than 80% mortality after 24 hours and 98% after 72 hours of application. The CAI , AZ M, MZM and DZA showed less toxicity (<50% mortality). Our results indicate that the CAI , including ETX in particular, is a worthy candidate as an alternative for the control of An. albimanus, which is considered a primary vector of malaria in Colombia.